We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
67
2
avatar

x-5-(2-x)= -3

 Oct 2, 2019
 #1
avatar+969 
+2

x-5-(2-x) = -3

You can use the distributive property on the -(2-x) so that -1*2 = -2 and -1*-x=x, so -(2-x) = -2+x

x-5-2+x = -3

2x-7=-3

 

Can you solve it from here?

 

You are very welcome!

:P

 Oct 2, 2019
 #2
avatar+2390 
0

Good job!

CalculatorUser  Oct 3, 2019

11 Online Users

avatar